1978
DOI: 10.1128/aac.14.6.807
|View full text |Cite
|
Sign up to set email alerts
|

HR 756, a Highly Active Cephalosporin: Comparison with Cefazolin and Carbenicillin

Abstract: HR 756, a new parenteral cephalosporin, was compared with cefazolin and carbenicillin for activity against a total of 264 strains ofPseudomonas aeruginosa, Escherichia coli, Klebsiella spp., Proteus mirabilis, Proteus spp. (indole positive), Enterobacter spp., Salmonella typhi, Serratia marcescens, Providencia stuartii, and Staphylococcus aureus. In every comparison, except that with the last organism, HR 756 was clearly more active than cefazolin and carbenicillin. All three compounds had similar activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 9 publications
7
36
0
Order By: Relevance
“…Cefamandole, in this and other studies (3,13), has been shown to have good in vitro activity against gram-positive cocci VOL. 19,1981 on April 7, 2019 by guest http://aac.asm.org/ Downloaded from (2,14,26) and moxalactam (7,15,25). Ro and cefotaxime were approximately equal in activity, with moxalactam being only slightly less active.…”
Section: Discussionmentioning
confidence: 98%
“…Cefamandole, in this and other studies (3,13), has been shown to have good in vitro activity against gram-positive cocci VOL. 19,1981 on April 7, 2019 by guest http://aac.asm.org/ Downloaded from (2,14,26) and moxalactam (7,15,25). Ro and cefotaxime were approximately equal in activity, with moxalactam being only slightly less active.…”
Section: Discussionmentioning
confidence: 98%
“…The novel cephalosporin, cefotaxime (HR756; CEF) has been shown by in vitro studies to be a potent antimicrobial agent (1,2,4) and is at present under clinical evaluation. It is known that CEF, like cephalothin, undergoes desacetylation in vivo ( Fig.…”
mentioning
confidence: 99%
“…Ongoing surveillance in our hospital did not identify an epidemic of nosocomial infections due to pseudomonas in association with the instances of superinfection with this organism which we observed. Whether the emergence of resistance to cefotaxime and other cephalosporins by serial in vitro passage of pseudomonas and other clinical isolates, as observed by Wise et al (26), has any relevance to our observations of superinfections with cefotaxime-resistance gram-negative bacilli during therapy with this drug awaits further study. Furthermore, the adequacy of monotherapy with cefotaxime for serious pseudomonas and other gram-negative bacillary infections requires additional observations, despite the 70% response rate of the 10 gram-negative bacillary pneumonias which we observed.…”
Section: Discussionmentioning
confidence: 84%